The Comprehensive Evaluation of the Coke Formation and Catalyst Deactivation in the Propane Dehydrogenation Reactor: Computational Fluid Dynamics Modelling - Soleiman Mosleh; Parviz Darvishi (Journal of Chemical and Petroleum Engineering, 2022)
A numerical evaluation was performed to understand the effect of catalytic bed geometry on the catalyst deactivation and propane dehydrogenation reactor performance with respect to coke formation. Furthermore, the temperature distribution and propane conversion along the reactor were studied. The governing equations with appropriate initial and boundary conditions were solved numerically, while two different bed arrangements (i.e. rectangular and parallelogram) were evaluated to find the optimized geometry in order to avoid the creation of hot spots. Findings indicated that parallelogram arrangement causes more conversion percentage owing to more axial as well as the radial mixing of reactants compared to the rectangular arrangement. Moreover, the obtained numerical results revealed that the optimum operating temperature to achieve the maximum conversion is 550 °C. As the temperature increases from 450 ºC to 650 ºC, the conversion of propane increases from 68.15% to 99.51%, during the reactor length. When the temperature exceeds above the optimum operating temperature, hot spots are created due to coke formation and also accumulation of coke on the catalyst bed surface that will lead to the deactivation of catalysts. The results of this work can be useful to examine the eﬀects of operating conditions to better understand physical and chemical phenomena occurring in the propane dehydrogenation reactor.